2015
DOI: 10.1176/appi.ps.201400212
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Functioning One Year After Experiencing Accumulated Coercive Events During Psychiatric Admission

Abstract: (2015). Quality of life and functioning one year after experiencing accumulated coercive events during psychiatric admission. Psychiatric Services, 66, 883-7. Corresponding AuthorStephen Shannon stshanno@gmail.com Abstract ObjectivesTo determine: the number of accumulated coercive events during admission and associations, functioning and quality of life one year after discharge and associations and whether accumulated coercive events were related to these outcomes. MethodsA prospective cohort study at three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Quality of life was not significantly influenced by previous involuntary admissions, a finding also found in other studies (89, 90). In the study by Ohlenschlaeger et al, the patients in integrated treatment, who are not directly comparable to our study due to the focus on patients of the first episode, showed a better quality of life compared to other treatment models (91).…”
Section: Discussionsupporting
confidence: 89%
“…Quality of life was not significantly influenced by previous involuntary admissions, a finding also found in other studies (89, 90). In the study by Ohlenschlaeger et al, the patients in integrated treatment, who are not directly comparable to our study due to the focus on patients of the first episode, showed a better quality of life compared to other treatment models (91).…”
Section: Discussionsupporting
confidence: 89%